One small step - Chedd, Graham , \eauthor (Boston, Mass. : WBGH Educational Foundation, 1988)
Examines the history of space exploration up to July 1975, when the Soviet Soyuz and the American Apollo rendezvoused and docked in space. Also explores the future of space exploration
Keywords: Outer space -- Exploration; Astronautics -- International cooperation